Assessment of Architectural Typologies and Comparative Analysis of Defensive Rammed Earth Dwellings in the Fujian Region, China - Xiuhong Lin; Yukun Zhang; Yilin Wu; Yingqian Yang (Buildings)
Tulou, Tubao, and Zhailu all belong to the same vernacular architectural defensive rammed earth dwellings in Fujian; however, because of the similarity of their earthen defensive functions and fortress architectural systems, they are easily confused by scholars and there is still a gap in distinguishing the in-depth differences between the three. For the first time, this article develops a proper architectural typology with a comparative analysis of five aspects (origin and prototype, plan and type, building function and settlement typology, structure type and construction technology, and ethical concept and settlement model) to distinguish their architectural features. We find that they have different architectural prototypes and plan types. Tubao is a defensive dwelling with a residential function, Tulou is a defensive dwelling with a residential function, and Zhailu is a dwelling that combines living and defense. They have six different structural types. Although Tulou has the simplest structure and the thinnest rammed earth wall, its construction technology is the best. Tubao and Zhailu have more clearly defined architectural levels than Tulou, and Tubao’s hierarchy is the most significant. Therefore, we prove that despite their similarities, they are different types of buildings. This study helps to provide a methodological guide for identifying other, similar buildings and serves as a manual for the restoration and sustainable development of defensive rammed earth dwelling.